2020
DOI: 10.3390/ijerph17031116
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Correlates of Ghosting and Breadcrumbing Experiences: A Preliminary Study among Adults

Abstract: The present study aimed to examine differences in three psychological constructs (satisfaction with life, loneliness, and helplessness) among adults experiencing ghosting and breadcrumbing. A sample of 626 adults (303 males and 323 females), aged from 18 to 40 years, completed an online survey asking to indicate whether someone they considered a dating partner had ghosted or breadcrumbed them in the last year and to complete three different scales regarding satisfaction with life, loneliness, and helplessness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 42 publications
2
49
2
17
Order By: Relevance
“…A growing amount of research has focused on the relationship dissolution strategy of ghosting. Prior research has sought to define ghosting (Koessler et al, 2019b; LeFebvre et al, 2019), explore rates and perceptions of ghosting (Freedman et al, 2019; LeFebvre, 2017), understand motivations for using ghosting (Koessler et al, 2019a, 2019b; LeFebvre et al, 2019, 2020), describe reactions to ghosting experiences (LeFebvre & Fan, 2020; Manning et al, 2019, Timmermans et al, 2020), and has begun to explore individual differences in ghostees and ghosters (Freedman et al, 2019; Navarro et al, 2020). This set of studies had two purposes: (1) to broaden the research on individual differences in ghosting by examining the association between ghosting experiences and attachment, and (2) to replicate prior research on individual differences that had demonstrated an association between ghosting experiences and implicit theories of relationships.…”
Section: Discussionmentioning
confidence: 99%
“…A growing amount of research has focused on the relationship dissolution strategy of ghosting. Prior research has sought to define ghosting (Koessler et al, 2019b; LeFebvre et al, 2019), explore rates and perceptions of ghosting (Freedman et al, 2019; LeFebvre, 2017), understand motivations for using ghosting (Koessler et al, 2019a, 2019b; LeFebvre et al, 2019, 2020), describe reactions to ghosting experiences (LeFebvre & Fan, 2020; Manning et al, 2019, Timmermans et al, 2020), and has begun to explore individual differences in ghostees and ghosters (Freedman et al, 2019; Navarro et al, 2020). This set of studies had two purposes: (1) to broaden the research on individual differences in ghosting by examining the association between ghosting experiences and attachment, and (2) to replicate prior research on individual differences that had demonstrated an association between ghosting experiences and implicit theories of relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be considered that the online lives of adolescents exhibit age-specific characteristics (often using different platforms) compared with those of adults (Biolcati, 2010). With regard to ghosting, a previous study (Navarro et al, 2020) found no significant differences according to gender or current sentimental status (single or having a partner) among the participants. Accordingly, men and women did not differ in ending a relationship by disappearing.…”
Section: Tablementioning
confidence: 71%
“…While we cannot experimentally study the situations described in the vignettes, it is possible that participants would act differently in these situations. For example, despite the fact that many of the participants in this study flatly denied being willing to ghost short-term romantic partners, we know that many young adults do in fact engage in ghosting (Freedman et al, 2019;LeFebvre et al, 2019;Navarro et al, 2020). As such, further investigation of what leads to such passive rejection-and how it may be affected by current mood states-is warranted.…”
Section: Discussionmentioning
confidence: 86%